A generalized input impedance model of multiple active bridge converter - Yang, Jiajun; Buticchi, Giampaolo; Gu, Chunyang; Gunter, Sandro; Zhang, He; Wheeler, Pat (2020)
The electrical power distribution system (EPDS) of the more electric aircraft (MEA) is a fundamental component that needs to be efficient and resilient. The commonly considered architectures feature separate buses to achieve separation between different subsections of the EPDS. Although effective, this implies an over design, since all subsections are sized for the local worst case scenarios. In the MEA concept, multiport converters could connect the whole EPDS while guaranteeing the galvanic isolation between buses. Since multiport converters would give rise to a completely different EPDS topology, dominated by power electronics interfaces, the stability of such a system must be assessed. This article investigates the input impedance of multiple active bridge (MAB) converters when interfaced with a single dc bus and multiple resistive loads. A transfer function-based input impedance model of the MAB converter is proposed. To validate the proposed input impedance model, the verification of input impedances of a triple active bridge (TAB) converter and a quadruple active bridge (QAB) converter is carried out using both simulation and experimental results. © 2015 IEEE.